Optimalisasi Edukasi Nutrisi 1000 Hari Pertama Kehidupan untuk Mencegah Stunting di Desa Arjasa Kecamatan Arjasa - Amini, Stefia Aisyah; Wahyukundari, Melok Aris; Syahirah, Diva Rana; Putri, Dhiani Eka; Adriana, Putu Julio; Dwisaraswati, Salma Aulia; Fitri, Amira Qanitah; Wijaya, Clarissa; Ramadhan, Takbir Sabda Akhiru; Hayati, Chairy; Arzani, Tiara Putri (Universitas Mataram, 2024)
The prevalence of stunting in Jember remains high, with Arjasa being one of the areas with significant incidence rates. The 2019 nutritional status estimate report for toddlers showed that one of village in Jember namely Arjasa had a high prevalence of stunting, at 44.1% of 663 children. Existing research indicates that Arjasa has a family stunting risk level based on maternal factors of 85.90%. These maternal factors include low maternal knowledge about nutrition and the ability to provide nutritious food during the first 1000 days of life. Therefore, this community service aims to educate mothers and prospective mothers in Arjasa on the importance of optimizing nutrition during the first 1000 days of life. The methods used include educating young women on healthy mother preparation, socializing stunting and its detection to Arjasa's posyandu cadres, socializing healthy 1000 HPK nutrition to pregnant women's communities, and developing local MSMEs. All activities went smoothly with each target event being attended. Post-test results showed an increase in knowledge and understanding of target subjects after providing the material. The activity received positive responses from village officials and Arjasa's posyandu, and was well-received by the local community. The community's knowledge related to stunting and improving 1000 HPK nutrition began to increase, but in practice, it still needed to cover all branch posyandu in Arjasa. In the future, it is expected that there will be more adequate facilities and infrastructure to cover more target subjects.